The Influence Of Village Fund Management On Infrastructure Development In Tanjung Anom Village - Situmorang, Melanti Donaria; Ramadhan, Puja Rizqy; Tripriyono, Agus (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine and analyze the influence of village fund management on infrastructure development in Tanjung Anom Village. The type of research used is associative research. The population in this study includes all residents of Tanjung Anom Village, totaling 4,303 people. The sampling technique was carried out using the probability sampling method, resulting in a sample of 98 respondents from the Tanjung Anom Village community. Data collection was carried out through observation, interviews, questionnaires, and documentation studies (literature). Data analysis was carried out using multiple linear regression, hypothesis testing, and classical assumption tests that include normality, heteroscedasticity, and multicollinearity. The results of the study indicate that village fund management has a significant influence on infrastructure development in Tanjung Anom Village.